Effect of structural instability on creep of zirconium subjected to severe plastic deformation - Frolov, V.A; Sokolenko, V.I.; Matz, A.V.; Karaseva, E.V. (Вопросы атомной науки и техники, 2014)
The peculiarities creep and electro-physical characteristics of zirconium subjected to severe plastic deformations by rolling on the different degrees at 300 K was studied. It is shown that in the process of creep of zirconium due to changes in the conditions of deformation the structure, which was created by rolling, becomes unstable. A plastic flow is carried out because of structure rearrangement at joint action of several mechanisms and accompanied by
stress relaxation. Изучены особенности ползучести и электрофизические характеристики циркония, подвергнутого интенсивным пластическим деформациям прокаткой при 300 К разной степени. Показано, что вследствие изменения условий деформирования в процессе ползучести циркония возникает нестабильность структурного со-
стояния, созданного прокаткой. В результате пластичное течение осуществляется за счет перестройки дефектной структуры и сопровождается релаксацией напряжений. Пластическая деформация сильно деформированного циркония обусловлена общим действием нескольких механизмов. Вивчено особливості повзучості та електрофізичні характеристики цирконію, підданого інтенсивним
пластичним деформаціям прокаткою при 300 К різної ступені. Показано, що внаслідок зміни умов
деформування в процесі повзучості цирконію виникає нестабільність структурного стану, створеного
прокаткою. В результаті пластична течія здійснюється за рахунок перебудови дефектної структури і
супроводжується релаксацією напруг. Пластична деформація сильно деформованого цирконію обумовлена
спільною дією декількох механізмів.